Developing inhibitors of bromodomain-histone interactions - Hewings, D (2014)
Lysine acetylation is a widespread protein post-translational modification that influences diverse cellular processes. An association between acetylation of histone N-terminal tails and transcriptional activation has been recognised since the 1960s. However, it has only become apparent since 2000 that many of the effects of histone acetylation are mediated by proteins that bind to acetyl-lysine through a specialised acetyl-lysine recognition domain, the bromodomain. Small-molecule inhibitors of bromodomain-histone interactions can greatly assist studies into the functions of bromodomain-containing proteins, and show promise as treatments for several diseases, including cancers. Herein I describe the discovery and development of a novel chemical series of bromodomain-binding ligands containing the 3,5-dimethyisoxazole moiety. This heterocycle acts as an acetyl-lysine bioisostere, mimicking key interactions formed between acetyl-lysine and the bromodomain. Optimised compounds show sub-micromolar affinities for bromodomains of the BET family, a class of transcriptional co-regulators. Crystallographic and structure-activity relationship studies shed light on the structural requirements for potent and selective BET ligands. Furthermore, the compounds show cellular effects consistent with BET bromodomain inhibition: cytotoxicity studies in a range of cell lines, including the NCI-60 human tumour cell line screen, reveal differential activity, with leukaemias showing particular sensitivity. 3,5-Dimethylisoxazole-containing compounds were also shown to downregulate known BET target genes. Further studies investigated the effect of modifying or replacing the methyl groups of 3,5-dimethylisoxazole on BET bromodomain affinity, which indicated that the 3-methyl group is necessary for affinity. Finally, three novel isoxazole-containing amino acids were synthesised and incorporated into histone peptides as potential bromodomain-binding, non-hydrolysable, acetyl-lysine mimics. These amino acids might be useful in uncovering the function of individual acetylated lysine residues. The identification of methyl-isoxazoles as acetyl-lysine-mimetic bromodomain ligands represents a significant advance in our understanding of structure-activity relationships for these important proteins. The confirmed cellular activity of these compounds will enable their use in future biological studies.